‘Straight bloody slaughter’ – the normalisation of violent conservation through exclusionary framing practices in South African newspaper coverage of rhino poaching - Hilliard-Lomas, Caitlyn Dominique (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.